A design analysis of piezoelectric-polymer composite-based valveless micropump. (3rd April 2019) - Revathi, S.; Padmapriya, N.; Padmanabhan, R.
ABSTRACT: This paper presents the three-dimensional numerical simulation of a micropump, including diffuser and analytical modelling of the micropump flow rate. The numerical simulation of the diffuser is performed in all possible flow regimes to optimize its geometry for maximum efficiency. The deflection of the piezoelectric polymer composite circular actuator is analytically solved by theory of bending plates to determine the volumetric change and flow rate. The result is then extended for actuator bonded to diaphragm of the micropump considering it as bilaminar plates. From the simulation results, it is found that and the diffuser angle >30° results in flow recirculation and reduction in the efficiency. The flow rate of the micropump obtained from analytical model and the numerical simulation are found to be similar.